2016
DOI: 10.1186/s12967-016-0894-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Th17 cells and IL-17A exist in patients with B cell acute lymphoblastic leukemia and promote proliferation and resistance to daunorubicin through activation of Akt signaling

Abstract: BackgroundImmune regulation is crucial for the pathogenesis of B-cell acute lymphoblastic leukemia (B-ALL). It has been reported that Th17 cells as a newly identified subset of CD4+ T cells are involved in the pathogenesis of several hematological disorders. However, the role of Th17 cells in the pathophysiology of B-ALL is still unclear.MethodsThe frequencies of T cells were determined by flow cytometry in the peripheral blood and bone marrow of 44 newly diagnosed B-ALL patients and 25 age-matched healthy don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…Therefore, the use of mTOR inhibitors could further blunt immunological responses against leukemic cells. However, another recent report demonstrated that an Akt inhibitor counteracted Th17 cell-induced resistance to daunorubicin in a preclinical model of B-ALL [ 181 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of mTOR inhibitors could further blunt immunological responses against leukemic cells. However, another recent report demonstrated that an Akt inhibitor counteracted Th17 cell-induced resistance to daunorubicin in a preclinical model of B-ALL [ 181 ].…”
Section: Discussionmentioning
confidence: 99%
“…We could identify 94 gene products and 47 molecular pathways that had close to 1 AUC scores for the ALL-normal comparison (Supplementary dataset S4, Table 1). Among those, branches of Akt signaling [24], cAMP [25], cytoplasmic and mitochondrial apoptosis [26], PTEN [27], ATM checkpoint [28], Hedgehog [29], HGF [30], GSK3 [31], Estrogen and Glucocorticoid reception [32, 33], IGF1R [34], IL2 [35], TNF [36], ILK [37], JAK-STAT [38], JNK [39], mTOR [40], TGF-beta [41], Ras [42], PPAR [43], NGF [44], VEGF [45], Wnt [46], HIF1 and Notch signaling [47] were previously reported in the literature as ALL-associated pathways. However, the identified GPCR and TRAF-associated apoptosis marker pathways were new, thus representing ~4% of the total ALL-specific pathways.…”
Section: Resultsmentioning
confidence: 99%
“…T h cell-derived cytokines can act on BCP-ALL cells as well, albeit with diverse effects. IL-2, IL-17 and IL-21, e.g., have been found to stimulate proliferation [83,93], while IL-4 and IL-13 inhibited BCP-ALL cell growth [88,[94][95][96], and IL-4 as well as TGF-β-induced apoptosis [97,98]. Cell-cell contact of BCP-ALL cells and activated allogenic T h cells induced activation and maturation of BCP-ALL cells [99].…”
Section: Malignant T H Cell-b Cell Interaction: Precursor B Cell Acutmentioning
confidence: 99%